Teaching Vocabulary Using Digital Storytelling: A Quasi-Experimental Study - Pratiwi, Handari; Bunau, Eusabinus; Rosnija, Eni (Journal of English Language and Education, 2026)
Vocabulary mastery is essential in English language learning because it supports students’ ability to understand and express ideas effectively. However, students often experience difficulties in mastering past-tense verbs due to the continued use of conventional teaching methods that emphasize memorization. This study aims to examine the effectiveness of digital storytelling in teaching past-tense verbs to tenth-grade students at SMAN 3 Bengkayang. Using a quasi-experimental design, the participants consisted of two groups: an experimental group and a control group, each consisting of 24 students. The data were collected through parallel 30-item cloze tests administered before and after the treatment and were analyzed using a t-test. The results showed that the experimental group demonstrated a significant improvement in vocabulary mastery, while the control group showed no significant increase. It can be concluded that digital storytelling is an effective instructional medium for improving students’ mastery of past-tense verbs in EFL classrooms.